EFEKTIFITAS BELAJAR DARING MAHASISWA PADA STIA ALAZKA AMBON - David O Roos (Program Studi Administrasi Publik, 2021)
Awareness of the Covid 19 pandemic has made all aspects of human life change drastically, this can be seen in changes in the lifestyle of humans which can be seen from their daily activities. The habit of acting before the Covid 19 pandemic is different from the habits that occurred after the emergence of the Covid 19 pandemic which can be seen from the various ways that were taken to prevent the transmission of this Covid outbreak. Therefore, through this study the author tries to find the effectiveness of online learning in students with various benefits and obstacles. Online lectures have various impacts on students' abilities. E Learning becomes a reference for the government to prevent and overcome transmission. The phenomenon of changing behavior and habits is the focus of research on the effectiveness of student online learning.